Primary cutaneous anaplastic large-cell lymphoma in a patient with Hodgkin's disease - case report - Dorota Kozłowska; Anna Baran; Iwona Flisiak (Termedia Publishing House, 2016)
Introduction. Cutaneous anaplastic large cell lymphoma (C-ALCL) is one of the CD30+ lymphoproliferative disorders. Usually it has a mild course and does not require aggressive treatment. The prognosis in C-ALCL is good, with the 10-year survival rate reaching 90% of patients. Spontaneous remissions of the disease are possible. Objective. To present a patient with recurrent Hodgkin's disease, in whom primary cutaneous anaplastic large cell lymphoma was diagnosed. Case report. A 35-year old woman with recurrent Hodgkin's disease was admitted to the department for diagnosis and treatment of skin lesions, which appeared a few weeks ago. Primary cutaneous T-cell lymphoma was diagnosed by histopathology and immunohistochemistry. After two weeks spontaneous regression of skin lesions was observed. Conclusions . Larger diagnostic procedures and exclusion of the systemic form of ALCL, cutaneous metastases of Hodgkin's disease and large-cell transformation of mycosis fungoides are required due to the aggressive course and different treatment in all cases.